Fifth national summit of health and population scientists: proceeding report; april 10-12, Kathmandu, Nepal (2019)
SUMMARY: The Fifth National Summit on Health and Population Scientists in Nepal (10-12 April 2019) was successfully completed by support of more than 1300 participants, 26 invited speakers, 69 oral presentations and 104 poster presentations. The summit was enriched with various Committees such as Advisory Committee of 36 persons, Steering Committee of 28 persons, Scientific Committee of 61 persons and Organizing Committee of 71 persons. On the first day, Pre-Summit conference was held that comprised of two Plenary Sessions, one Panel Discussion, one Symposium and one Interaction. Similarly, on 2nd and 3rd Day there was Inauguration session (by Hon. Dr. Surendra K. Yadav, State Minister, MoHP), Key note address (by Prof. Dr. Balram Bhargava, Director General, ICMR, New Delhi and Secretary, Department of Health Research, Ministry of Health and Family Welfare, Government of India), two Plenary Sessions (on each day), eight Parallel Sessions (4 in each day) and Closing Session (by Hon. Upendra Yadav, Deputy PM & Health Minister). At a glance, total number of Invited speakers were 27 among which 19 speakers were from Nepal, 3 speakers from India, 3 speakers from China, 1 from Germany and 1 from the USA. There were 69 oral presentations, 26 invited talk and 93 poster presentations in summit covering diverse issues including Communicable and Non-Communicable Diseases; Maternal, Neonatal, Child, Adolescent, Geriatric and Migrant Health; Biomedical and Anti-Microbial Resistance; Ayurveda and Other Traditional Medicine; Environmental and Occupational Health; Mental Health and Substance Abuse; Community Based NCDs Management; Biomedical and Health Information Technology; Health System, Health Economics and Financing; Health Promotion, Technology and Essential Medical Products; Health, Equity and Development; Health Insurance; Sexual and Reproductive Health and Family Planning; Disabilities, Injuries and Critical Care; Nutrition and Food Safety and many more. These issues are closely related to attainment of comprehensive and ambitious SDGs. The Collaborative Partners were, MoHP, UK-AID, NHSSP, WHO, UNICEF, GIZ, Strengthening System for Better Health Activity, Golden Community, IPAS Nepal, VSO, Care Nepal, Save the Children, One Heart World Wide, CREPHA, Nepal Development Society, TPO Nepal, HERD International, The Leprosy Mission Nepal, Sunaulo Pariwar Nepal, Marie Stopes International. In the award session, the best awardees were selected based on the contribution, creativity and innovation. JNHRC Best Paper Award 2018 was given to titled, 'Prevalence of Cardiovascular Risk Factors in Apparently Healthy Urban Adult Population of Kathmandu' to Dr. Om Murti Anil, Outstanding Health Research Award 2018 was given to Dr. Shamshul Ansari, Mrigendra Samjhana Medical Trust Young Health Researcher Award (Medical Doctor) was given to Dr. Pranil Man Singh Pradhan, Mrigendra Samjhana Medical Trust Young Health Research Award (NHRC Staff) was given to Mr. Bihungum Bista, Health Research Life-time Achievement Award was given to Prof. Dr. Shiba Kumar Rai, Best Employee Performance Award of the NHRC was given to Mr. Pradeep Belbase, NHRC's employee near to retirement Award was given to Mr Ram Prasad Pokharel, Best Oral Presentation Award was given to Prof Dr. Nisha Jha and Best Poster Presentation Award was given to Mr. Pushpa Chand Thakuri. The declaration of the summit was presented at the end of the summit. The session was concluded with remarks from the executive chairperson of Nepal Health Research Council. The overwhelming presence of more than 1300 participants is the reflection of the fact that the summit is a common platform of health professionals to come through latest development in the field of health research.